PERAN DIGITALISASI DESA TERHADAP PERTUMBUHAN EKONOMI DI DESA KRANDEGAN, JAWA TENGAH - Stefanus Rahoyo; Masine Slahanti; Bambang Heriawan (Universitas Kristen Satya Wacana, 2023)
This study aims to analyze the process of village digitization and its influence on economic growth in Krandegan Village, Central Java. Using a qualitative approach, this study found that the digitization of the village occurred because it was driven by a village head who had an entrepreneurial spirit, was supported by the millennial generation who were literate and responsive to digital technology, and was accelerated by the Covid-19 momentum. Furthermore, from an economic standpoint, the direct impacts of village digitalization are opening up market opportunities, increasing village income through BUMDES, and opening up job opportunities. Meanwhile, the indirect impacts of it are the flow of various aid and the opening of networks. All of these impacts ultimately increase village economic activity and growth.